The great orchestrator : Arthur Judson and American arts management - Doering, James M. (Music in American life., 2013)
This biography charts the career and legacy of the pioneering American music manager Arthur Judson (1881-1975), who rose to prominence in Philadelphia and New York at the beginning of the twentieth century.